Circumplex Models of Personality and Emotions.
DOI: 10.1037/10261-012
|View full text |Cite
|
Sign up to set email alerts
|

The interpersonal circle and the emotional undercurrents of human sociability.

Abstract: My interest in the circumplex model of interpersonal traits started when I read Leary's (1957) Interpersonal Diagnosis of Personality in the early 1970s. I was seeking a theoretical background to my dissertation topic, which concerned interpersonal responses given to a projective test styled after Rosenzweig's ( 1945) Picture Frustration Test. 1 was impressed-and still am-by the simultaneous richness and clarity of Leary's book: It offered a fascinatingly elaborate picture of the social side of personality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…Tracey (1994) examined the validity of Carson's (1969) definition with Strong et al's (1988) orientation of dimensions versus Wiggins's (1979) definition of complementarity at the behavioral interchange level and found Carson's definition with Strong et al's orientation superior in accounting for complementary behavioral interchanges. This study extends this past research by increasing the number of alternative models examined (adding two more orientations, Leary's [1957] and Myllyniemi's [1997] and applying these to the trait level rather than the behavioral interchange level).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Tracey (1994) examined the validity of Carson's (1969) definition with Strong et al's (1988) orientation of dimensions versus Wiggins's (1979) definition of complementarity at the behavioral interchange level and found Carson's definition with Strong et al's orientation superior in accounting for complementary behavioral interchanges. This study extends this past research by increasing the number of alternative models examined (adding two more orientations, Leary's [1957] and Myllyniemi's [1997] and applying these to the trait level rather than the behavioral interchange level).…”
mentioning
confidence: 64%
“…The complement would need to have a granting of love status to the other and removal of love and status Different definitions of complementarity. SOURCE: Leary (1957), Myllyniemi (1997), Strong et al (1988), and Wiggins (1995). NOTE: Complementary behaviors are indicated by dark, bold lines.…”
mentioning
confidence: 99%
“…First, in line with the training protocol developed by [74] the observers were instructed to move the joystick to the correct location in the Cartesian plane in response to 16 interpersonal adjectives, such as warm, trusting, passive, unsociable, indifferent, critical, assertive and outgoing. Then, the observers carried out a similar exercise with images of facial expressions; the images were drawn from the study by [59], who has shown that the idea of the interpersonal circumplex applies also to facial expressions of emotion. Finally, the observers heard one-sentence-long verbal descriptions of interactional events, in response to which they needed to move the joystick to the correct location in the Cartesian plane (see the electronic Supplementary information).…”
Section: Training Procedures For Observersmentioning
confidence: 99%
“…Circumplex models have been used to describe other interpersonal domains including facial expressions (Myllyniemi, 1997), vocational interests (Tracey & Rounds, 1997), parent-child relations (Schaefer, 1997), social acuity or empathy (Gurtman, 1997) and social support (Wiggins & Trobst, 1997).…”
Section: Offence Narrative Roles and Their Relationship To The Emotiomentioning
confidence: 99%